Behavioral evidence for inter-hemispheric cooperation during a lexical decision task: a divided visual field experiment - Perrone-Bertolotti, Marcela; Lemonnier, Sophie; Baciu, Monica (Frontiers in Human Neuroscience, 2013)
This study explores inter-hemispheric interaction during a lexical decision task by using a behavioral approach, the bilateral presentation of stimuli within a divided visual field experiment. Previous studies have shown that compared to unilateral presentation, the bilateral redundant presentation decreases the inter-hemispheric asymmetry and facilitates the cooperation between hemispheres. However, it is still poorly understood which type of information facilitates this cooperation. In the present study, verbal stimuli were presented unilaterally (left or right visual hemi-field successively) and bilaterally (left and right visual hemi-field simultaneously). Moreover, during the bilateral presentation of stimuli, we manipulated the relationship between target and distractors in order to specify the type of information which modulates the inter-hemispheric interaction. Thus, three types of information were manipulated: perceptual, semantic, and decisional, respectively named pre-lexical, lexical and post-lexical processing. Our results revealed left hemisphere lateralization during the lexical decision task. In terms of inter-hemisphere interaction, the perceptual and decision-making information increased the inter-hemispheric asymmetry, suggesting the inhibition of one hemisphere upon the other. In contrast, semantic information decreased the inter-hemispheric asymmetry, suggesting cooperation between the hemispheres. We discussed our results according to current models of inter-hemispheric interaction and concluded that cerebral hemispheres interact and communicate according to various excitatory and inhibitory mechanisms, all which depend on specific processes and various levels of word processing.